Structural and Functional Characterization of Acetoacetate Decarboxylase-Like Enzymes - (:unkn) unknown (My University, 2016)
The acetatoacetate decarboxylase-like superfamily (ADCSF) is a largely unexplored group of enzymes that may be a potential source of new biocatalysts. Bioinformatic analysis has grouped these approximately 2000 enzymes into seven different families based on comparison of predicted active site residues. To date, only the prototypical ADCs (Family I) that catalyze the decarboxylation of acetoacetate have been studied. Analysis of gene context suggests that Family V contains predominantly enzymes predicted to be involved in secondary metabolism. On average, these share about 20% sequence identity to the true ADCs. To learn more about the diversity of chemistries performed by members of Family V, we have been studying two enzymes annotated as "acetoacetate decarboxylase" in the GenBank database. These are Sbi_00515 from Streptomyces bingchenggensis and Swit_4259 from Sphingomonas wittichii. Steady state analyses of these enzymes demonstrate that both lack decarboxylase activity with any of the substrates tested. This was surprising given that the crystal structures of both enzymes show that their overall folds are almost indistinguishable from that of the prototypical ADCs, though the quaternary structures are different. An important observation from the bioinformatic and crystallographic analyses is that the catalytic lysine and putative acid/base catalyst residues of the true ADCs are retained in both groups of enzymes, but the active site architectures are different. Specifically, two residues shown to be important for the acetoacetate decarboxylase reaction, Arg29 and Glu61 in Clostridium acetobutylicum ADC (CaADC), are not retained in the Family V enzymes. Site-directed mutagenesis, steady state and transient kinetics, and mass spectroscopy data suggest evidence for reversible aldolase-dehydratase and retro-aldolase activities mediated through a Schiff-base mechanism. These are the first Schiff-base-forming aldolases that do not use the TIM barrel fold. Although the physiologically relevant reactions of these Family V enzymes are unknown, these studies illustrate that the ADC fold is a versatile platform that can be adapted to perform different chemistries.